The use of foods and dietary supplements with antioxidant activity in the elderly - Miguel Henrique Pereira de Paiva, Mayara Rafaela dos Reis, Maria da Conceição Calassa Albuquerque, Judite Oliveira Lima Albuquerque, Vicente Galber Freitas Viana (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v3i3.1498